Prospek dan Tantangan Ekspor Indonesia ke Pasar Non-Tradisional: Mengukur Daya Saing Produk Indonesia di Pasar UEA - Nurhafizhah, Riska; Hirawan, Fajar B (Jurusan Ilmu Administrasi Publik, Universitas Lampung, 2021)
The US-China Trade War and the COVID-19 pandemic are unprecedented incidents involving Indonesia's traditional markets as the main actors, i.e. the US and China which impacted Indonesia's economy and trade indirectly. Market diversification to new market or non-traditional market is one way out that can be done to minimize the impact of the global crisis on the country, when traditional markets are unreliable, such as the United Arab Emirates (UAE) that has made a positive contribution both in investment and trade for Indonesia in the midst of a pandemic. However, Indonesia's exports to the UAE experienced a significant decline in 2018 after theprevious two years continued to increase. So that knowing the competitiveness of Indonesia's export products in the UAE is the purpose of this study. This research answers the prospects and challenges of Indonesian export products in the UAE by measuring the export performance in 2016-2018 using the Constant Market Share (CMS) and Revealed Comparative Advantage (RCA) analysis methods. This research uses descriptive quantitative method with secondary data and triangulation of data sources, methods, and theories as the validity and reliability methods. The results of this study indicate that the results of CMS and RCA are different so that the prospects and challenges for Indonesian products are also explained by the Indonesian approach and trade policies which lead to the conclusion that the UAE is a potential market to become non-traditional market for Indonesian economic development when its traditional markets are unreliable.